Mathematikbezogene Kompetenzentwicklung elementarpädagogischer Fachpersonen in Intensiv-Fortbildungen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Entwicklung eines videobasierten Instruments zur Erhebung von Handlungsfähigkeiten elementarpädagogischer Fachpersonen im mathematischen Bereich (VimaH) - Bruns, Julia; Eichen, L. (Entwicklung mathematischer Fähigkeiten von Kindern im Grundschulalter – Tagungsband des AK Grundschule in der GDM 2015)

Entwicklung eines videobasierten Instruments zur Erhebung mathematikdidaktischer Handlungskompetenzen elementarpädagogischer Fachpersonen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Adaptive Förderung zur Vorbereitung auf den Übergang vom Elementar- in den Primarbereich am Beispiel des Bereichs Mathematik - Bruns, Julia; Eichen, Lars (Frühe Bildung)
Die vorliegende quasi-experimentelle Querschnittsuntersuchung verfolgt das Ziel, adaptive Förderleistungen elementarpädagogischer Fachpersonen zu erfassen und Zusammenhänge mit anderen Komponenten elementarpädagogischer Arbeit aufzudecken. Im Zentrum steht die Frage: Welcher Zusammenhang zeigt sich zwischen der Beobachtungsintensität, den diagnostischen Fähigkeiten und der Qualität der adaptiven Förderpraxis im Elementarbereich? Fokussiert wird die adaptive Förderleistung einer Teilstichprobe mit n = 31 Fachpersonen in Bezug auf die Teilstichprobe von n = 62 Kinder. Dazu werden verschiedene Methoden auf Kinder- und Fachpersonenebene im Sinne eines mixed-methods Designs miteinander verknüpft (Mathematiktest ‚zahlenstark‘, standardisierte Beobachtung, standardisiertes Interview). Die Ergebnisse zeigen, dass keiner Fachperson eine optimale Förderung zweier Kinder gelingt. Im Hinblick auf den Übergang zwischen Elementar- und Primarbereich kann gefolgert werden, dass die Kinder unzureichend in ihren individuellen Bildungsprozessen begleitet werden.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Betonen – Ignorieren – Gegensteuern? Zum pädagogischen Umgang mit Geschlechtstypiken.
Im Kontext von Schule sind gleichzeitig offensiv geschlechterbetonende wie auch Geschlechterstereotypen wiedersprechende Maßnahmen zu finden. In diesem Buch sollen diese widersprüchlichen Tendenzen verstanden und die Konsequenzen für den pädagogischen Alltag aufgezeigt werden. Den Hintergrund des Buches bildet die Beobachtung, dass momentan gleichzeitig offensiv geschlechterbetonende wie auch Geschlechterstereotypen widersprechende und ausgleichende Maßnahmen im Kontext von Schule zu finden sind – und eine zunehmende Vielfalt von geschlechterbetonenden Marktangeboten. Im Rahmen eines vom BMBF geförderten Projekts sind Wissenschaftler/innen und Fachkräfte aus der Praxis zusammengekommen, um diese aktuellen Auffälligkeiten zu diskutieren. Im Zentrum steht das Anliegen, diese widersprüchlichen Tendenzen zu verstehen, es geht aber ebenso um die Frage, wie sie im pädagogischen Alltag beantwortet werden können und sollten.

Erkenntnis, Wissen, Intervention - Geschlechterwissenschaftliche Perspektiven
Der Band beschäftigt sich aus einer feministischen Perspektive mit Wechselwirkungen zwischen Erkenntnis, Wissen und Intervention auf wissenschaftlicher und gesellschaftlicher Ebene. Von jeher war es zentrales Anliegen feministischer Theoriediskurse, durch Veränderungen der Wissensbestände in Alltag und Wissenschaften neue und andere Erkenntnisprozesse zu ermöglichen und sie als Intervention in gesellschaftliche Machtverhältnisse und Alltagsroutinen wissenschaftlich und politisch produktiv werden zu lassen. Mit der doppelten Bewegung von Erkenntnis und Wissen als Intervention und Intervention in Erkenntnis, Wissen und Gesellschaft befassen sich alle Beiträge des vorliegenden Bandes. Sie nehmen Dynamiken und Wechselbeziehungen zwischen Erkenntnis, Wissen und Intervention auf wissenschaftlicher und gesellschaftlicher Ebene sowie mit Blick auf unterschiedliche Felder auf.

The optical properties of low infrared transmittance WO3-x nanocrystal thin films prepared by DC magnetron sputtering under different oxygen ratios - Xin, Y.; Zhou, H.; Ni, X.; Pan, Ying; Zhang, X.; Zheng, J.; Bao, S.; Jin, P. (RSC Advances)

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups? - Ortmann, Regina (Die Betriebswirtschaft)

Investitionsneutrale Besteuerung des ökonomischen Gewinns: ein Abriss jüngerer Forschungsbeiträge - Diller, Markus; Grottke, Markus; Lorenz, Johannes (Wirtschaftswissenschaftliches Studium (WiSt))

Tax Aggressiveness of Taxpayers with Heterogenous Income and Uncertainty about Taxable Income - Diller, Markus; Lorenz, Johannes (FinanzArchiv / Public Finance Analysis)

Frankreich – Bewegung, Spiel und Sport der Heranwachsenden bei unserem Nachbarn - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, H.P. (Dritter Kinder- und Jugendsportbericht. Kinder- und Jugendsport im Umbruch)

Interkulturelle (Bewegungs-)Erziehung – Vom sportpädagogischen Konzept zum überfachlichen Fragebogen - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Zeitschrift für sportpädagogische Forschung)

Missachtungsprozesse unter Schülerinnen und Schülern im Sportunterricht. Sportdidaktische Konsequenzen aus einem multimethodischen Forschungsprojekt - Grimminger-Seidensticker, Elke (sportpädagogik)

Über die Bedingung der Möglichkeit historisch-kritischer Methode als Traditionskritik in der islamischen Theologie - Ghaffar, Zishan (Zwischen Glaube und Wissenschaft. Theologie in Christentum und Islam)

Geschichten vom ersten bis zum 38. Stock - Kostan, Anastassija (Turmgeschichten: Raumerfahrung und -aneignung im AfE-Turm)

Aging in digital circuits and age monitoring: Object-oriented modeling and evaluation - Sadeghi-Kohan, Somayeh; Kamran, Arezoo; Forooghifar, Farnaz; Navabi, Zainalabedin (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling resulting in timing variations and consequently reliability challenges in digital circuits. Age monitoring methods can be used to predict and deal with the aging problem. Selecting appropriate locations for placement of hardware aging monitors is an important issue. In this work we propose a procedure for selection of appropriate internal nodes in combinational clouds between pipeline stages or combinational parts of a sequential circuit to place hardware monitors that can effectively provide aging information of various components of a modern digital system. In order to implement the node selection procedure, we propose an object-oriented model. Object-oriented model of a circuit along with a probabilistic and logical simulation engine that we have developed can effectively be used for implementation and also fast evaluation of the proposed node selection mechanism. The proposed object-oriented C+ + models can be integrated into a SystemC RTL model making it possible to perform mixed-level simulation, and integrated evaluation of a complete system. We have applied our proposed scheme to several processors including MIPS, ARM, ALPHA and MiniRISC and have looked at its effectiveness for these processors.

Online self adjusting progressive age monitoring of timing variations - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; McNeil, John; Prinetto, Paolo; Navabi, Zain (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling that results in timing variations. Progressive age measurement of a circuit can help a better prevention mechanism for reducing more aging. This requires age monitors that collect progressive age information of the circuit. This paper focuses on monitor structures for implementation of progressive age detection. The monitors are self-adjusting that they adjust themselves to detect progressive changes in the timing of a circuit. Furthermore, the monitors are designed for low hardware overhead, and certainty in reported timing changes.

Automating RDF Dataset Transformation and Enrichment - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (12th Extended Semantic Web Conference, Portorož, Slovenia, 31st May - 4th June 2015)
With the adoption of RDF across several domains, come growing requirements pertaining to the completeness and quality of RDF datasets. Currently, this problem is most commonly addressed by manually devising means of enriching an input dataset. The few tools that aim at supporting this endeavour usually focus on supporting the manual definition of enrichment pipelines. In this paper, we present a supervised learning approach based on a refinement operator for enriching RDF datasets. We show how we can use exemplary descriptions of enriched resources to generate accurate enrichment pipelines. We evaluate our approach against eight manually defined enrichment pipelines and show that our approach can learn accurate pipelines even when provided with a small number of training examples.
Keywords: 2015 group_aksw sys:relevantFor:geoknow sys:relevantFor:infai sys:relevantFor:bis ngonga simba dice sherif group_aksw geoknow deer lehmann MOLE

Simplified RDB2RDF Mapping - Stadler, Claus; Unbehauen, Joerg; Westphal, Patrick; Sherif, Mohamed; Lehmann, Jens (Proceedings of the 8th Workshop on Linked Data on the Web (LDOW2015), Florence, Italy)
The combination of the advantages of widely used relational databases and semantic technologies has attracted significant research over the past decade. In particular, mapping languages for the conversion of databases to RDF knowledge bases have been developed and standardized in the form of R2RML. In this article, we first review those mapping languages and then devise work towards a unified formal model for them. Based on this, we present the Sparqlification Mapping Language (SML), which provides an intuitive way to declare mappings based on SQL VIEWS and SPARQL construct queries. We show that SML has the same expressivity as R2RML by enumerating the language features and show the correspondences, and we outline how one syntax can be converted into the other. A conducted user study for this paper juxtaposing SML and R2RML provides evidence that SML is a more compact syntax which is easier to understand and read and thus lowers the barrier to offer SPARQL access to relational databases.
Keywords: 2015 group_aksw group_mole mole stadler lehmann sherif simba dice sys:relevantFor:geoknow geoknow peer-reviewed MOLE westphal